Building a Health Literacy Indicator from Angola Demographic and Health Survey in 2015/2016 - Ramos, Neida Neto Vicente (2022)
Funding Information: We selected information from 19,785 adults aged 15–49 years old who responded to the survey. Data were collected between October 2015 and March 2016. The survey was conducted in all Angola provinces in Portuguese [25]. The use and dissemination of the data was authorized by the Demographic and Health Surveys program [24]. DHS surveys in Angola are funded by the United States Agency for International Development (USAID) and administered by the National Institute of Statistics in Angola (INE) in collaboration with the Angolan Ministry of Health (MINSA). Funding Information: Sa?de Global e Medicina Tropical, Instituto de Higiene e Medicina Tropical, Universidade Nova de Lisboa, Portugal, reference: UID/04413/2020. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.